2018
DOI: 10.1208/s12248-018-0242-5
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Optimal Designs for Dose–Response Studies Through Adaptive Randomization for a Small Population Group

Abstract: In dose-response studies with censored time-to-event outcomes, D-optimal designs depend on the true model and the amount of censored data. In practice, such designs can be implemented adaptively, by performing dose assignments according to updated knowledge of the dose-response curve at interim analysis. It is also essential that treatment allocation involves randomization-to mitigate various experimental biases and enable valid statistical inference at the end of the trial. In this work, we perform a comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Adaptive optimal designs can be cast in two or more stages and they have been developed and implemented in practice [16,17]. Since most phase II studies are randomized, controlled, parallel-group designs, careful choice of a randomization procedure that adjusts optimal allocation ratio at interim analyses is essential [95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive optimal designs can be cast in two or more stages and they have been developed and implemented in practice [16,17]. Since most phase II studies are randomized, controlled, parallel-group designs, careful choice of a randomization procedure that adjusts optimal allocation ratio at interim analyses is essential [95].…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of phase II studies are randomized, careful calibrations of a randomization procedure to implement the chosen optimal design is warranted. Ryeznik et al [94,95] investigated multi-stage adaptive D-optimal designs for dose-response studies with time-to-event outcomes. They found that both the choice of the allocation design and the randomization procedure can affect the quality of model estimates.…”
Section: Phase II Dose-ranging Studiesmentioning
confidence: 99%